The Influence of Twinning on the Strain–Hardenability in TRIP/TWIP Titanium Alloys: Role of Solute–Solution Strengthening - Danard, Yolaine; Sun, Fan; Gloriant, Thierry; Freiherr Von Thüngen, Immanuel; Piellard, Michaël; Prima, Frédéric (Frontiers in Materials, 2020)
TRIP/TWIP titanium alloys are well-known to display a good combination of strain-hardenability and ductility. However, a large range of strain-hardening rates, that cannot be predicted by the actual design method based on electronic parameters, is obtained. In order to explain this wide range of properties, two different alloys displaying a large difference of strain-hardening rates, but similar chemical stability, have been studied and compared: Ti-12Mo and Ti-8.5Cr-1.5Sn (in wt%). Evolution of both twin size and density during in-situ tensile tests have been followed by SEM/EBSD mapping and two distinct behaviors can be highlighted: the growth of existing twins (Ti-12Mo), and the nucleation of new twins (Ti-8.5Cr-1.5Sn) upon loading. The last one may lead to an improvement of the dynamic Hall-Petch effect by multiplication of twin/matrix interfaces, with subsequent improvement of the macroscopic strain-hardening. It is thought that this competition may be related to the crystal lattice distortion induced by the alloying elements and the subsequent reduction of the migration velocity of the twin/matrix interfaces.